Ultrahigh-film-thickness two-component epoxy iron red primer and application thereof
By using two-component combinations with specific ratios in epoxy primer, the problems of large film thickness and poor acid and alkali resistance in the existing epoxy primer are solved, and ultra-high film thickness is not sag and good acid resistance is achieved. Effects of alkaline properties.
Patent Information
- Application Number
- CN202411725696.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The dry film sag of existing epoxy primers is large in thickness, which is difficult to meet customers' requirements for film thickness. At the same time, there are problems with sagging and poor acid and alkali resistance.
Provide a two-component epoxy iron red primer with ultra-high film thickness. It ensures film thickness through a combination of main agent and curing agent with specific ratios, including AE-80 epoxy emulsion, JT-WBH818 curing agent and other components. It is between 140 and 220 μm and does not sag, and the acid and alkali resistance is improved.
It realizes that the epoxy primer with ultra-high film thickness does not sag, meets customers' requirements for film thickness, and maintains good acid and alkali resistance, reduces costs, and is suitable for industrial applications.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a two-component epoxy iron red primer with ultra-high film thickness and application thereof. Background Art
[0002] In rail transit coatings, the dry film sagging thickness of existing epoxy primers is mostly 80-100μm, and some are as high as 130μm. Customers require the primer to be 75-85μm thick. In order to pursue beauty, the primer must be polished flat after spraying, so the actual primer film thickness is 80-100μm. The film thickness at some places at the junction of spraying may reach 200μm. The consequences include: 1. Increase the risk of film sagging, 2. Increase the number of bubbles in the paint film, and increase the channels for other substances to corrode the substrate, which reduces the performance of the coating and puts the rail transit protection system at risk of failure. At present, the two-component epoxy iron red primer in the relevant technology has the problems of too thick film, sagging problem, too small film thickness, and poor acid and alkali resistance. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a two-component epoxy iron red primer with ultra-high film thickness and its application. The two-component epoxy iron red primer of the present invention has a large film thickness, does not sag, and has good acid and alkali resistance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a two-component epoxy iron red primer with ultra-high film thickness, comprising a main agent and a curing agent which are packaged separately.
[0006] The main agent comprises the following components in mass percentage: 35-45% AE-80 epoxy emulsion, 1-2% dispersant, 5-10% titanium dioxide, 5-15% mica powder, 5-10% wollastonite, 5-10% talc, 2-10% precipitated barium sulfate, 5-10% red iron oxide, 5-20% water, 0.2-0.5% thickener, 2-5% dipropylene glycol butyl ether (DPNB), 0.1-0.3% wetting agent, 0.3-0.5% silane coupling agent, 0.2-0.5% defoamer, and 0.2-1% wetting defoamer;
[0007] The curing agent comprises the following components in percentage by mass: 50-70% of JT-WBH818 curing agent, 25-45% of water, and 3-10% of anti-flash rust agent.
[0008] Preferably, the main agent includes the following components in mass percentage: 35% AE-80 epoxy emulsion, 2% dispersant, 5% titanium dioxide, 10% mica powder, 10% wollastonite, 5% talc, 5% precipitated barium sulfate, 10% red iron oxide, 13.2% water, 0.5% thickener, 3% dipropylene glycol butyl ether, 0.2% wetting agent, 0.3% silane coupling agent, 0.3% defoaming agent, and 0.5% wetting defoaming agent.
[0009] Preferably, the main agent includes the following components in mass percentage: 40% AE-80 epoxy emulsion, 2% dispersant, 5% titanium dioxide, 10% mica powder, 10% wollastonite, 5% talc, 5% precipitated barium sulfate, 10% red iron oxide, 8.2% water, 0.5% thickener, 3% dipropylene glycol butyl ether, 0.2% wetting agent, 0.3% silane coupling agent, 0.3% defoaming agent, and 0.5% wetting defoaming agent.
[0010] Preferably, the main agent includes the following components in mass percentage: 45% AE-80 epoxy emulsion, 2% dispersant, 5% titanium dioxide, 10% mica powder, 10% wollastonite, 5% talc, 5% precipitated barium sulfate, 10% red iron oxide, 5.2% water, 0.5% thickener, 1% dipropylene glycol butyl ether, 0.2% wetting agent, 0.3% silane coupling agent, 0.3% defoaming agent, and 0.5% wetting defoaming agent.
[0011] Preferably, the particle sizes of wollastonite and talc are both 1250 mesh.
[0012] Preferably, the mass ratio of the main agent to the curing agent is 5:1.
[0013] Preferably, the thickness of the two-component epoxy iron red primer is 140-220 μm.
[0014] Preferably, the thickness of the two-component epoxy iron red primer is 180-200 μm.
[0015] Preferably, the curing agent comprises the following components in percentage by mass: 60% of JT-WBH818 curing agent, 35% of water, and 5% of anti-flash rust agent RB60.
[0016] The present invention also provides the application of the ultra-high film thickness two-component epoxy iron red primer described in the above technical solution in the field of rail transportation.
[0017] The invention provides a two-component epoxy iron red primer with ultra-high film thickness. The primer comprises a main agent and a curing agent which are separately packaged. The main agent comprises the following components in mass percentage: 35-45% of AE-80 epoxy emulsion, 1-2% of dispersant, 5-10% of titanium dioxide, 5-15% of mica powder, 5-10% of wollastonite, 5-10% of talcum powder, 2-10% of precipitated barium sulfate, 5-10% of red iron oxide, 5-20% of water, 0.2-0.5% of thickener, 2-5% of dipropylene glycol butyl ether, 0.1-0.3% of wetting agent, 0.3-0.5% of silane coupling agent, 0.2-0.5% of defoaming agent and 0.2-1% of wetting defoaming agent; and the curing agent comprises the following components in mass percentage: 50-70% of JT-WBH818 curing agent, 25-45% of water and 3-10% of anti-flash rust agent.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] In the present invention, the AE-80 epoxy emulsion can increase the film thickness of the paint film without sagging, and can satisfactorily solve the problem of too thick film and sagging, so that the film thickness of the epoxy primer reaches 220 μm without sagging, and is matched with the JT-WBH818 curing agent, which does not affect the acid and alkali resistance. At the same time, it can reduce costs and is suitable for industrial applications. DETAILED DESCRIPTION
[0020] The invention provides a two-component epoxy iron red primer with ultra-high film thickness, comprising a main agent and a curing agent which are packaged separately.
[0021] The main agent comprises the following components in mass percentage: 35-45% AE-80 epoxy emulsion, 1-2% dispersant, 5-10% titanium dioxide, 5-15% mica powder, 5-10% wollastonite, 5-10% talc, 2-10% precipitated barium sulfate, 5-10% red iron oxide, 5-20% water, 0.2-0.5% thickener, 2-5% dipropylene glycol butyl ether, 0.1-0.3% wetting agent, 0.3-0.5% silane coupling agent, 0.2-0.5% defoamer, and 0.2-1% wetting defoamer;
[0022] The curing agent comprises the following components in percentage by mass: 50-70% of JT-WBH818 curing agent, 25-45% of water, and 3-10% of anti-flash rust agent.
[0023] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0024] In the present invention, the main agent preferably includes the following components in mass percentage: AE-80 epoxy emulsion 35%, dispersant 2%, titanium dioxide 5%, mica powder 10%, wollastonite 10%, talc 5%, precipitated barium sulfate 5%, red iron oxide 10%, water 13.2%, thickener 0.5%, dipropylene glycol butyl ether 3%, wetting agent 0.2%, silane coupling agent 0.3%, defoamer 0.3%, wetting defoamer 0.5%;
[0025] Or including the following components in percentage by mass: AE-80 epoxy emulsion 40%, dispersant 2%, titanium dioxide 5%, mica powder 10%, wollastonite 10%, talc 5%, precipitated barium sulfate 5%, red iron oxide 10%, water 8.2%, thickener 0.5%, dipropylene glycol butyl ether 3%, wetting agent 0.2%, silane coupling agent 0.3%, defoamer 0.3%, wetting defoamer 0.5%;
[0026] Or including the following components in percentage by mass: AE-80 epoxy emulsion 45%, dispersant 2%, titanium dioxide 5%, mica powder 10%, wollastonite 10%, talc 5%, precipitated barium sulfate 5%, red iron oxide 10%, water 5.2%, thickener 0.5%, dipropylene glycol butyl ether 1%, wetting agent 0.2%, silane coupling agent 0.3%, defoamer 0.3%, wetting defoamer 0.5%.
[0027] In the present invention, the particle sizes of wollastonite and talc are preferably both 1250 mesh.
[0028] In the present invention, the AE-80 epoxy emulsion is preferably purchased from Shanghai Shurui Chemical Technology Co., Ltd.
[0029] In the present invention, the dispersant is preferably BYK-190 dispersant.
[0030] In the present invention, the titanium dioxide is preferably titanium dioxide 706.
[0031] In the present invention, the mica powder is preferably GA-4 mica powder.
[0032] In the present invention, the thickener is preferably thickener 0620.
[0033] In the present invention, the wetting agent is preferably wetting agent 4100.
[0034] In the present invention, the silane coupling agent is preferably 915 silane coupling agent, which is preferably purchased from Tianjin Aoluqi Chemical Technology Co., Ltd.
[0035] In the present invention, the defoamer is preferably BYK-028 defoamer.
[0036] In the present invention, the wetting and defoaming agent is preferably 104E wetting and defoaming agent.
[0037] In the present invention, the water is preferably deionized water.
[0038] In the present invention, the mass ratio of the main agent to the curing agent is preferably 5:1.
[0039] In the present invention, the thickness of the two-component epoxy iron red primer is preferably 140-220 μm, more preferably 180-200 μm, and specifically can be 140, 160, 180, 200 or 220 μm.
[0040] In the present invention, the curing agent comprises the following components in percentage by mass: 60% of JT-WBH818 curing agent, 35% of water, and 5% of anti-flash rust agent.
[0041] In the present invention, the flash rust preventer is preferably the flash rust preventer RB60 (Raybo60 flash rust preventer from the United States).
[0042] In the present invention, the JT-WBH818 curing agent is preferably purchased from Tianjin Lingwei New Material Technology Co., Ltd.
[0043] The present invention has no special limitation on the preparation method of the ultra-high film thickness two-component epoxy iron red primer, and the primer can be prepared by a preparation method of a composition well known to those skilled in the art.
[0044] In the present invention, the preparation method of the main agent preferably comprises pre-mixing, grinding and blending performed in sequence.
[0045] In the present invention, preferably part of water, a wetting defoamer, a dispersant, titanium dioxide, red iron oxide, wollastonite, talcum powder, precipitated barium sulfate and mica powder are mixed for pre-refining to obtain a pre-refined material.
[0046] In a specific embodiment of the present invention, it is preferred to first add the part of water, start stirring, the dispersion frequency is 200 to 500 rpm, then add the wetting defoamer, stir for 2 to 3 minutes, and then add the dispersant, titanium dioxide, red iron oxide, wollastonite, talcum powder, precipitated barium sulfate and mica powder in sequence, stir for 3 to 5 minutes after each addition, and then add the next item, increase the stirring speed to 300 to 700 rpm, continue stirring for 15 minutes after adding, and complete the pre-refining.
[0047] After obtaining the pre-mixed material, the pre-mixed material is ground, and then flushed with the remaining water to obtain a grinding slurry.
[0048] The present invention has no particular limitation on the ratio of the partial water to the remaining water, and any ratio may be used.
[0049] In the present invention, the particle size of the polishing slurry is preferably ≤30 μm, more preferably ≤10 μm.
[0050] In the present invention, the grinding is preferably carried out in a sand mill, and the cooling water and slurry flow rates are adjusted so that the grinding temperature is preferably <50°C, the grinding pressure is preferably <0.2MPa, and monitoring and recording are preferably performed every 20 minutes; the grinding is carried out in an inverted cylinder, and the fineness is self-checked and recorded each time. After the fineness is below 30μm, samples are taken for inspection. If the fineness is qualified, the obtained pre-refined slurry is poured into a blending cylinder and ground with the remaining water to obtain a grinding slurry.
[0051] After obtaining the grinding slurry, the present invention mixes the grinding slurry, AE-80 epoxy emulsion, wetting agent, defoamer, thickener, silane coupling agent and dipropylene glycol butyl ether to obtain the main agent.
[0052] In a specific embodiment of the present invention, the AE-80 epoxy emulsion and the wetting agent are preferably added to a mixing cylinder containing a grinding slurry, dispersed at a speed of 300 to 700 rpm for 5 minutes, then a defoamer is added, the stirring speed is increased to 500 to 900 rpm, stirred for 60 to 90 minutes, the stirring speed is adjusted to 300 to 700 rpm, and then a thickener, a silane coupling agent and dipropylene glycol butyl ether are added in sequence, each item is stirred for 3 to 5 minutes before adding the next item, and finally stirred for 20 minutes, and samples are taken for inspection.
[0053] The present invention also provides the application of the ultra-high film thickness two-component epoxy iron red primer described in the above technical solution in the field of rail transportation.
[0054] The present invention has no particular limitation on the specific manner of the application, and any manner familiar to those skilled in the art may be used.
[0055] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] Preparation process of the main agent of ultra-high film thickness two-component epoxy iron red primer:
[0058] First add some water and start stirring at a dispersion frequency of 500 rpm, then add the wetting defoamer and stir for 3 minutes, then add the dispersant, titanium dioxide, red iron oxide, wollastonite, talcum powder, precipitated barium sulfate and mica powder in turn, stir for 5 minutes after each addition before adding the next item, increase the stirring speed to 700 rpm, continue stirring for 15 minutes after adding, and complete the pre-refining; grind the obtained pre-refined material, pass it through a sand mill, adjust the cooling water and slurry flow rate, make the grinding temperature 40°C, the grinding pressure 0.15MPa, monitor and record every 20 minutes, grind in an inverted cylinder, self-check the fineness each time and record, and grind. to below 30 μm, take samples for inspection, if the fineness is qualified, put the obtained pre-refined slurry into the mixing cylinder, grind with the remaining water to obtain the grinding slurry; add AE-80 epoxy emulsion and wetting agent into the mixing cylinder containing the grinding slurry, disperse at 700 rpm for 5 minutes, then add defoamer, increase the stirring speed to 900 rpm, stir for 90 minutes, adjust the stirring speed at 700 rpm, then add thickener, silane coupling agent and dipropylene glycol butyl ether in turn, stir for 5 minutes after adding each item, and finally stir for 20 minutes, take samples for inspection, and obtain the main agent of the ultra-high film thickness two-component epoxy iron red primer.
[0059] The main agent formulas of Examples 1 to 3 and Comparative Examples 1 to 3 are shown in Table 1. The resin in Examples 1 to 3 and Comparative Example 1 is AE-80 epoxy emulsion (purchased from Shanghai Shurui Chemical Technology Co., Ltd.), the resin in Comparative Example 2 is 3011 resin (purchased from Jiangsu Fuqisen New Materials Co., Ltd.), and the resin in Comparative Example 3 is 2092 resin (purchased from Lianku Chemical Group).
[0060] The preparation processes of Examples 2 to 3 and Comparative Example 1 are the same as that of Example 1, the only difference being the amount of raw materials used; the preparation processes of Comparative Examples 1 to 2 are the same as that of Example 1, the only difference being the type of resin used.
[0061] Table 1 Main agent formula (wt%) of Examples 1 to 3 and Comparative Examples 1 to 3
[0062] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Partially deionized water 12 7 4 17 12 12 104 Wetting and defoaming agent 0.5 0.5 0.5 0.5 0.5 0.5 BYK190 dispersant 2 2 2 2 2 2 Titanium Dioxide 706 5 5 5 5 5 5 Iron oxide red 10 10 10 10 10 10 1250 mesh wollastonite 5 5 5 5 5 5 1250 mesh talc 10 10 10 10 10 10 Precipitated barium sulfate 5 5 5 5 5 5 GA-4 Mica Powder 10 10 10 10 10 10 Remaining deionized water 1.2 1.2 1.2 1.2 1.2 1.2 Resin 35 40 45 30 35 35 4100 Wetting Agent 0.2 0.2 0.2 0.2 0.2 0.2 BYK-028 defoamer 0.3 0.3 0.3 0.3 0.3 0.3 0620 Thickener 0.5 0.5 0.5 0.5 0.5 0.5 915 silane coupling agent 0.3 0.3 0.3 0.3 0.3 0.3 Dipropylene glycol butyl ether 3 3 1 3 3 3
[0063] The curing agent in the embodiment and the comparative example is composed of the following components in percentage by mass: 60% of JT-WBH818 curing agent, 35% of water, and 5% of anti-flash rust agent RB60.
[0064] In the two-component epoxy iron red primer of the embodiment and the comparative example, the mass ratio of the main agent to the curing agent is 5:1.
[0065] Performance Test:
[0066] Acid and alkali resistance test standard: GB / T 9274.
[0067] The maximum sagging dry film thickness of Example 1 is 220μm, and there is no abnormality in acid and alkali resistance for 168h. The maximum sagging dry film thickness of Example 2 is 200μm, and there is no abnormality in acid and alkali resistance for 168h. The maximum sagging dry film thickness of Example 3 is 180μm, and there is no abnormality in acid resistance for 168h, and blistering occurs in alkali resistance for 168h. The maximum sagging dry film thickness of Comparative Example 1 is 200μm, and there is no abnormality in acid resistance for 168h, and blistering occurs in alkali resistance for 168h. The maximum sagging dry film thickness of Comparative Example 2 is 160μm, and blistering occurs in acid and alkali resistance for 168h. The maximum sagging dry film thickness of Example 3 is 150μm, and blistering occurs in acid and alkali resistance for 168h. It can be seen that the sagging film thickness of the experimental data of Example 1 is the highest, and the acid and alkali resistance performance is excellent.
[0068] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A two-component epoxy iron red primer with ultra-high film thickness, characterized in that: Including independent packaging of main agent and curing agent, The main agent comprises the following components in mass percentage: 35-45% AE-80 epoxy emulsion, 1-2% dispersant, 5-10% titanium dioxide, 5-15% mica powder, 5-10% wollastonite, 5-10% talc, 2-10% precipitated barium sulfate, 5-10% red iron oxide, 5-20% water, 0.2-0.5% thickener, 2-5% dipropylene glycol butyl ether, 0.1-0.3% wetting agent, 0.3-0.5% silane coupling agent, 0.2-0.5% defoamer, and 0.2-1% wetting defoamer; The curing agent comprises the following components in percentage by mass: 50-70% of JT-WBH818 curing agent, 25-45% of water, and 3-10% of anti-flash rust agent.
2. The two-component epoxy iron red primer according to claim 1, characterized in that: The main agent includes the following components in percentage by mass: 35% AE-80 epoxy emulsion, 2% dispersant, 5% titanium dioxide, 10% mica powder, 10% wollastonite, 5% talc, 5% precipitated barium sulfate, 10% red iron oxide, 13.2% water, 0.5% thickener, 3% dipropylene glycol butyl ether, 0.2% wetting agent, 0.3% silane coupling agent, 0.3% defoaming agent, and 0.5% wetting defoaming agent.
3. The two-component epoxy iron red primer according to claim 1, characterized in that: The main agent comprises the following components in percentage by mass: 40% AE-80 epoxy emulsion, 2% dispersant, 5% titanium dioxide, 10% mica powder, 10% wollastonite, 5% talc, 5% precipitated barium sulfate, 10% red iron oxide, 8.2% water, 0.5% thickener, 3% dipropylene glycol butyl ether, 0.2% wetting agent, 0.3% silane coupling agent, 0.3% defoaming agent, and 0.5% wetting defoaming agent.
4. The two-component epoxy iron red primer according to claim 1, characterized in that: The main agent comprises the following components in percentage by mass: 45% AE-80 epoxy emulsion, 2% dispersant, 5% titanium dioxide, 10% mica powder, 10% wollastonite, 5% talc, 5% precipitated barium sulfate, 10% red iron oxide, 5.2% water, 0.5% thickener, 1% dipropylene glycol butyl ether, 0.2% wetting agent, 0.3% silane coupling agent, 0.3% defoaming agent, and 0.5% wetting defoaming agent.
5. The two-component epoxy iron red primer according to any one of claims 1 to 4, characterized in that: The particle sizes of the wollastonite and talc are both 1250 meshes.
6. The two-component epoxy iron red primer according to any one of claims 1 to 4, characterized in that: The mass ratio of the main agent to the curing agent is 5:
1.
7. The two-component epoxy iron red primer according to any one of claims 1 to 4, characterized in that: The thickness of the two-component epoxy iron red primer is 140-220 μm.
8. The two-component epoxy iron red primer according to claim 7, characterized in that: The thickness of the two-component epoxy iron red primer is 180-200 μm.
9. The two-component epoxy iron red primer according to claim 1, characterized in that: The curing agent comprises the following components in percentage by mass: 60% of JT-WBH818 curing agent, 35% of water, and 5% of anti-flash rust agent.
10. Use of the ultra-high film thickness two-component epoxy iron red primer according to any one of claims 1 to 9 in the field of rail transportation.
Citation Information
Patent Citations
Water-based epoxy intermediate paint
CN101104770A
Multifunctional low-surface treatment epoxy thick slurry long-effect anticorrosive primer and preparation method thereof
CN108690468A
Environment-friendly low-surface-treatment water-based epoxy thick paste type acid and alkali resistant coating and preparation method thereof
CN112552779A
Waterborne epoxy emulsion, high-film-thickness epoxy primer and preparation method of high-film-thickness epoxy primer
CN115594864A
Water-based two-component epoxy primer for rail transit coating and preparation method of water-based two-component epoxy primer
CN118879159A